2019
DOI: 10.1152/japplphysiol.00122.2019
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-independent alterations in muscle activation and effort perception during forearm exercise: role of local oxygen delivery

Abstract: The oxygen-conforming response (OCR) of skeletal muscle refers to a downregulation of muscle force for a given muscle activation when oxygen delivery (O2D) is reduced, which is rapidly reversed when O2D is restored. We tested the hypothesis that the OCR exists in voluntary human exercise and results in compensatory changes in muscle activation to maintain force output, thereby altering perception of effort. In eight men and eight women, electromyography (EMG), oxyhemoglobin (O2Hb) and deoxyhemoglobin (HHb), fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…However, the difference in EMG amplitudes was maintained at similar levels to control trials with significantly higher muscle activation during high versus low J Physiol 598.20 fibre recruitment exercise. Partial occlusion of blood flow is previously shown to increase muscle activity (Drouin et al 2019) which can explain the observed increase in EMG amplitudes during BaCl 2 administration. Furthermore, venous [K + ] and forearm K + efflux were higher in both exercise patterns compared to resting values, as expected.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…However, the difference in EMG amplitudes was maintained at similar levels to control trials with significantly higher muscle activation during high versus low J Physiol 598.20 fibre recruitment exercise. Partial occlusion of blood flow is previously shown to increase muscle activity (Drouin et al 2019) which can explain the observed increase in EMG amplitudes during BaCl 2 administration. Furthermore, venous [K + ] and forearm K + efflux were higher in both exercise patterns compared to resting values, as expected.…”
mentioning
confidence: 71%
“…Partial occlusion of blood flow is previously shown to increase muscle activity (Drouin et al . 2019) which can explain the observed increase in EMG amplitudes during BaCl 2 administration. Furthermore, venous [K + ] and forearm K + efflux were higher in both exercise patterns compared to resting values, as expected.…”
Section: Figure Underlying Mechanisms Involved In Exercise‐induced Vamentioning
confidence: 82%
“…The goal was to apply enough compression pressure to reduce radial artery blood velocity by 40 -50% and maintain that pressure for 2 min. The use of this arterial compression model to reduce blood velocity and shear rate has been utilized by others (8,17,37,38,44). Although others have used a pneumatic piston or linear actuator device to apply constant pressure to the brachial artery during the compression at rest (37,38), this approach is less feasible during exercise because of subject movement (38).…”
Section: Methodsmentioning
confidence: 99%
“…This model has previously been used at rest and during rhythmic handgrip exercise to reduce shear rate (8,37,38,44) and downstream oxygen delivery . The major advantage of this approach over the more conventional cuff occlusion technique is that arterial oxygen delivery is reduced without disrupting venous return, which can alter local skeletal muscle hemodynamics as well as systemic hemodynamics via the metaboreflex (1,10,17,34). We hypothesized that, during compression, NIR-DCS would effectively track reductions in skeletal muscle microvascular perfusion (measured by DCS) and compensatory reductions in tissue saturation (i.e., increased oxygen extraction) (measured by NIRS) to maintain skeletal muscle oxygen consumption throughout exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Although the reasons for this are unclear, we have previously shown that intra-arterial administration of BaCl 2 does not affect maximal voluntary contraction force (Crecelius et al 2013a). Interestingly, Drouin et al (2019) recently reported rapid increases in muscle activation when blood flow to the exercising tissue was partially occluded. Thus, it is possible that compromised blood flow and oxygen delivery during BaCl 2 administration resulted in greater muscle activation for a given workload.…”
Section: Muscle Activationmentioning
confidence: 99%